2004
DOI: 10.1108/01443570410532579
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel case study critique of six sigma: statistical control or strategic change?

Abstract: 2002),"Critical success factors for the successful implementation of six sigma projects in organisations", The TQM Magazine, Vol. 14 Iss 2 pp. 92-99 http:// dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
129
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 34 publications
1
129
0
5
Order By: Relevance
“…Cross-functionality of communication and collaboration have been identified as a key factor for a successful LSS project (Choi et al, 2012). People recognition through empowerment, inspiration and involvement in decision making processes have always been an important and challenging cultural construct of successful implementation of LSS (Kanpp, 2015;Antony, 2014;Hilton and Sohal, 2012;Daily et al, 2012;Baird et al, 2011;Zu and Fredendall, 2009;McAdam and Lafferty, 2004). Some empirical research has found support for this argument; for example, Kanpp (2015) and Jimenez-Jimenez and Martinez-Costa (2009) have recommended employees' involvement in decision making and giving flexibility and responsibility to employees as significant constructs to initiate any quality improvement practice.…”
Section: Organisational Culture and Readiness For Lssmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-functionality of communication and collaboration have been identified as a key factor for a successful LSS project (Choi et al, 2012). People recognition through empowerment, inspiration and involvement in decision making processes have always been an important and challenging cultural construct of successful implementation of LSS (Kanpp, 2015;Antony, 2014;Hilton and Sohal, 2012;Daily et al, 2012;Baird et al, 2011;Zu and Fredendall, 2009;McAdam and Lafferty, 2004). Some empirical research has found support for this argument; for example, Kanpp (2015) and Jimenez-Jimenez and Martinez-Costa (2009) have recommended employees' involvement in decision making and giving flexibility and responsibility to employees as significant constructs to initiate any quality improvement practice.…”
Section: Organisational Culture and Readiness For Lssmentioning
confidence: 99%
“…Lean Six Sigma (LSS) is a business improvement strategy that has flourished over the last decade because of its promise of enhanced business performance and market capability. LSS has evolved through the combination of Lean and Six Sigma, both recognised as leading total quality management (TQM) tools for performance improvement in organisations with a proper infrastructure built on leadership and change culture (Dora and Gellynck, 2015;Assarlind et al, 2013;Wang and Chen, 2012;Choi et al, 2012;Hilton and Sohal, 2012;Atmaca and Girenes, 2013;Lee et al, 2011;Delgado et al, 2010;Dahlgaard and Dahlgaard-Park, 2006;McAdam and Lafferty, 2004). LSS is now regarded as one of the most effective and disciplined business transformation initiatives available in strategic operations management as well as an effective top-down methodology for improving quality in both the manufacturing and service small-and medium-sized enterprise (SMEs) and their larger counterparts (Kanpp, 2015;Isa and Usmen, 2015, Bhat et al, 2014, Algassem et al, 2014Biranvand and Khasseh, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six`Sigma offers a solid statistical methodology for experimentation and research [46]. In fact, the definition given by Linderman et al [20] indicate that the initiatives for improvement were grounded in powerful statistical methods.…”
Section: Statistical Process Control (Spc)mentioning
confidence: 99%
“…Given that, the research is based in a single case study setting, there are limits on the degree to which the conclusions can be generalized (Nonthaleerak and Hendry, 2008). McAdam and Lafferty (2004) conducted a survey in a single company on Six Sigma implementation issue from process and people perspective. They found low success of Six Sigma in nonmanufacturing areas.…”
Section: Introductionmentioning
confidence: 99%